Outcomes in patients diagnosed with tongue cancer before and after the age of 45 years. (November 2020) - Mizuno, Kayoko; Takeuchi, Masato; Kikuchi, Masahiro; Omori, Koichi; Kawakami, Koji
Highlights: This retrospective cohort study included 2315 tongue cancer patients. We included 1412 patients in the multivariable Cox proportional hazards modeling. Overall survival was not significantly different between young and old patients. Young patients should be treated in accordance with guidelines. Abstract: Objective: Whether the prognosis of tongue cancer differs between young patients and elderly patients remains controversial. We aimed to compare the clinical characteristics and prognoses of patients with young-onset and old-onset tongue cancer. Materials and methods: The retrospective cohort study utilized data from the Diagnosis Procedure Combination database maintained in Japan. Data derived from patients age ≥ 20 years diagnosed with tongue cancer between April 2008 and January 2019 were extracted from the database. Patients were divided into two groups based on age at tongue cancer diagnosis, a < 45 years group and a ≥ 45 years group. The primary outcomes were overall survival and disease-free survival, adjusted for age, sex, tumor classification, nodal metastasis, distant metastasis, smoking history, Charlson Comorbidity Index score, and tongue cancer treatment. Results: A total of 2315 patients diagnosed with tongue cancer were included in the study, of whom 1412 patients diagnosed based on the seventh edition of the Union for International Cancer Control in the multivariable Cox proportional hazards modeling. The adjusted hazard ratio for overall survival was 1.22 (95% confidence interval 0.66–2.24, p  = 0.54) and that for disease-free survival was 1.14 (95% confidence interval 0.80–1.61, p  = 0.47), and neither differed significantly between the two age groups. Conclusions: The results of the present study suggest that younger age at the time of tongue cancer diagnosis may not be associated with a poorer prognosis. Young patients with tongue cancer should be treated in accordance with general guidelines.